(untitled) (Publicaciones en Ciencias y Tecnología, 2019)
Artificial intelligence is projected as a new factor of production to improve the competitiveness of countries. This research analyzes the technical efficiency of the application of Artificial Intelligence (AI) as a production factor in companies located in Europe, North America, Asia and Latin America aimed at increasing their competitiveness. Research data on the impact of AI in the world economies, figures on startups, the global index of innovation and investments in AI are taken. Through Data Envelopment Analysis (DEA) the technical efficiency is measured. The analysis was structured in three clusters: by countries with and without China, and by regions with companies with investments in AI. The analysis by countries showed that Holland, Sweden, Chile, and Colombia are more efficient, while the USA, Japan, and Brazil are less efficient. With respect to the second analysis, China and Latin America stand out as efficient. For the latter case, Europe and Latin America proved efficient. It is observed that the growth in the global index of innovation, as well as the creation of economic policies in countries for the development of this technology, are keys to predicted economic growth.